Optical identification of sulfur vacancies: Bound excitons at the edges of monolayer tungsten disulfide - Carozo, Victor (Sci Adv, 2017)
Defects play a significant role in tailoring the optical properties of two-dimensional materials. Optical signatures of defect-bound excitons are important tools to probe defective regions and thus interrogate the optical quality of as-grown semiconducting monolayer materials. We have performed a systematic study of defect-bound excitons using photoluminescence (PL) spectroscopy combined with atomically resolved scanning electron microscopy and first-principles calculations. Spatially resolved PL spectroscopy at low temperatures revealed bound excitons that were present only on the edges of monolayer tungsten disulfide and not in the interior. Optical pumping of the bound excitons was sublinear, confirming their bound nature. Atomic-resolution images reveal that the areal density of monosulfur vacancies is much larger near the edges (0.92 ± 0.45 nm(−2)) than in the interior (0.33 ± 0.11 nm(−2)). Temperature-dependent PL measurements found a thermal activation energy of ~36 meV; surprisingly, this is much smaller than the bound-exciton binding energy of ~300 meV. We show that this apparent inconsistency is related to a thermal dissociation of the bound exciton that liberates the neutral excitons from negatively charged point defects. First-principles calculations confirm that sulfur monovacancies introduce midgap states that host optical transitions with finite matrix elements, with emission energies ranging from 200 to 400 meV below the neutral-exciton emission line. These results demonstrate that bound-exciton emission induced by monosulfur vacancies is concentrated near the edges of as-grown monolayer tungsten disulfide.